Sistema para a oferta de serviços baseados em localização com garantias de privacidade do usuário - Ribeiro, Filipe Nunes (2009)
The use of geographical information about users is the main quality of Location Based Services (LBS). Services like finding nearest hotels and restaurants, weather forecasting or traffic conditions verifying are some of them that can be found without hard effort. Even though using LBS can be bring out facilities and benefits, manipulation of location information by malicious parties can represent serious threat to users privacy. The mobile telephony has been widely used to offer LBS, mainly due to the powerful increase of mobile devices, location capabilities in the devices and the large number of potential users. Despite the existence of techniques to offer privacy in LBS execution, there is no much interest in using these techniques in the mobile telephony environment, besides, the majority of proposed techniques do not present results that can be used in a real environment. This work presents a system that offers location privacy to mobile phone applications. The expression location privacy points out the competency of avoid that third parties learn about current or past location of the user. Then, we propose the Location Privacy Based System (SBPL), that offers manners to control location information release and allows LBS execution with privacy guarantees to mobile phone users. The SBPL is composed by a client application, performed in the mobile device, and a trusted server, acting between the mobile device and the service provider. Besides, the SBPL follows the recommendations of existing privacy guidelines, and allows the user to determine his preferences, which assure adaptation to distinct users and services. Tests were performed in LBS environments that prove the efficiency of SBPL and the possibility of using it in the mobile phone environment.